2016
DOI: 10.1021/acsnano.6b06091
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties of Phase-Pure and Polytypic Colloidal Semiconductor Quantum Wires

Abstract: We report ensemble extinction and photoluminesence spectra for colloidal CdTe quantum wires (QWs) with nearly phase-pure, defect-free wurtzite (WZ) structure, having spectral line widths comparable to the best ensemble or single quantum-dot values, to the single polytypic (having WZ and zinc blende (ZB) alternations) QW values, and to those of two-dimensional quantum belts or platelets. The electronic structures determined from the multifeatured extinction spectra are in excellent agreement with the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…4b) using the method similar to the literatures. 20,36,37 It was interesting that the extracted bandgaps of Zn 1Àx Mn x S nanowires did not shown a linear relationship with the composition x, but exhibited a nonlinear optical bowing effect (Fig. 4c) similar to that reported in PbS x Se 1Àx nanocrystals 38 and ZnSe x Te 1Àx nanowires, 20 etc.…”
Section: Resultssupporting
confidence: 52%
“…4b) using the method similar to the literatures. 20,36,37 It was interesting that the extracted bandgaps of Zn 1Àx Mn x S nanowires did not shown a linear relationship with the composition x, but exhibited a nonlinear optical bowing effect (Fig. 4c) similar to that reported in PbS x Se 1Àx nanocrystals 38 and ZnSe x Te 1Àx nanowires, 20 etc.…”
Section: Resultssupporting
confidence: 52%
“…The spectrum closely resembled those reported previously for CdTe quantum wires. 8,27,28 The positions of the four prominent features were extracted by peak fitting (Figure S4) and were shifted to longer wavelength (by about 20 nm) than the corresponding features for polytypic (zinc blende, wurtzite mixed phase) CdTe quantum wires having a mean diameter of 6.5 nm. 27 This result suggested that the quantum wires prepared here were of slightly larger diameter.…”
Section: Resultsmentioning
confidence: 99%
“…17−19 A huge step toward control of the phase purity of solutiongrown NWs has been achieved recently by the solution-solidsolid (SSS) approach. 20,21 Here, it was proposed that specific precursor and surfactant chemistry leads to conditions where the Bi catalyst particle is in a solid state. In particular, it has been shown that either almost phase-pure WZ NWs can be synthesized if the Cd precursor is prepared from CdO in a DOPT (di-n-octylphosphinate)/n-tetradecyl-phosphonate (TDPT) mixture or alternating WZ/ZB NWs are obtained from CdO dissolved in n-tetradecylphosphonic acid (TDPA) only.…”
Section: ■ Introductionmentioning
confidence: 99%